What SDO tells us about structure and evolution of coronal bright points. Issue 10 (December 2014) - Karachik, N. V.; Minenko, E.; Sattarov, I.; Pevtsov, A. A.; Sherdonov, C. T.
Abstract Using magnetograms and coronal images from two instruments on board the Solar Dynamics Observatory (SDO), we study structure and evolution of a limited number of coronal bright points (CBPs). Our results show that the relation between CBPs and their magnetic footpoints is not simple. In some cases, CBP may appear as a bright portion of a larger loop (with clearly identifiable footpoints), and in some cases, an isolated CBP may develop between magnetic poles, which might not be the closest ones to each other or which might not be involved in the magnetic flux cancellation. We suggest that the magnetic connectivity responsible for formation of isolated coronal bright points is governed by the orientation of the large‐scale magnetic field. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)